2019 IEEE Symposium on Security and Privacy (SP) 2019
DOI: 10.1109/sp.2019.00014
|View full text |Cite
|
Sign up to set email alerts
|

How Well Do My Results Generalize? Comparing Security and Privacy Survey Results from MTurk, Web, and Telephone Samples

Abstract: Security and privacy researchers often rely on data collected from Amazon Mechanical Turk (MTurk) to evaluate security tools, to understand users' privacy preferences and to measure online behavior. Yet, little is known about how well Turkers' survey responses and performance on security-and privacy-related tasks generalizes to a broader population. This paper takes a first step toward understanding the generalizability of security and privacy user studies by comparing users' selfreports of their security and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
67
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(79 citation statements)
references
References 46 publications
1
67
0
Order By: Relevance
“…We surveyed 502 individuals in a convenience sample from Mechanical Turk. Table 2 summarizes our participants' demographics, which we compare to those of a recent study by Redmiles et al [20] comparing sampling methods. Our participant population skewed male.…”
Section: Participant Demographicsmentioning
confidence: 99%
See 1 more Smart Citation
“…We surveyed 502 individuals in a convenience sample from Mechanical Turk. Table 2 summarizes our participants' demographics, which we compare to those of a recent study by Redmiles et al [20] comparing sampling methods. Our participant population skewed male.…”
Section: Participant Demographicsmentioning
confidence: 99%
“…In spite of this, most participants appeared to understand the mathematical concepts we presented to them. We tested participants' understanding of the graphs in our survey with a series of [20]. A dash indicates that the study did not use that particular category.…”
Section: Participant Demographicsmentioning
confidence: 99%
“…While MTurk is widely used, Prolific is explicitly set up for academic research studies. Analyses have shown that MTurk yields reasonable results, even though not adhering to strict standards of experimental design [27]. Research has shown that participants from Prolific are more equally distributed across the world, and tend to answer more honest than people from MTurk while the data quality is comparable [23].…”
Section: B Recruitmentmentioning
confidence: 99%
“…One reason for the paucity of research on social components of youth activities may be previous methodological constraints. However, recent advances in technology such as Amazon's Mechanical Turk (MTurk) provide reliable and efficient online platforms for collecting psychological and other data [60,65]. MTurk offers a flexible, easy-to-implement method for "crowdsourcing" opinions [15], such as those about the dynamics of socialand non-social youth activities.…”
mentioning
confidence: 99%